1993
DOI: 10.1007/bf02073383
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of umbilical arterial versus umbilical venous blood PH correlated with arterio-venous glucose difference and cardiotocographic score

Abstract: The value of clinical parameters and umbilical arterial blood pH as indicator of prenatal hypoxia is disputed. In a prospective study of 86 vaginally delivered full-term infants, cardiotocographic (CTG) findings obtained 0-30 min and 30-60 min before birth were compared to pH values, O2 and CO2 partial pressures and glucose difference in umbilical arterial and venous blood. CTG findings were expressed as a score, higher values indicating fetal hypoxia. The venous but not the arterial blood pH was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Moreover, differences in the two vascular loops with regard to the composition of cord blood constituents, blood flow and degree of oxygenation may play a role. Importantly, the venous blood composition of the fetoplacental unit depends on net exchange of available substrates between mother and placenta, while arterial blood composition is influenced foremost by fetal metabolism [ 38 , 39 ]. The intrinsic factors in parallel with the metabolic disturbances in arteries and veins in GDM [ 40 , 41 ] may account for differences and susceptibility towards GDM programming.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, differences in the two vascular loops with regard to the composition of cord blood constituents, blood flow and degree of oxygenation may play a role. Importantly, the venous blood composition of the fetoplacental unit depends on net exchange of available substrates between mother and placenta, while arterial blood composition is influenced foremost by fetal metabolism [ 38 , 39 ]. The intrinsic factors in parallel with the metabolic disturbances in arteries and veins in GDM [ 40 , 41 ] may account for differences and susceptibility towards GDM programming.…”
Section: Discussionmentioning
confidence: 99%
“…The serum glucose levels may also increase because of fetal hypoxia [50]. Chen et al [37] showed that high serum glucose levels may be a reliable marker of fetal stress and may also have a negative effect in newborn's wish to get breast-feeded.…”
Section: Laborduration(hours)mentioning
confidence: 98%
“…Neonatal asphyxia was considered when the Apgar scores in the first and fifth minute of life were lower than 7 and venous umbilical pH < 7.20. The umbilical venous pH was utilized as a criteria for fetal acidemia because it is always 0.04-0.08 higher than umbilical arterial pH, it is easily obtained even in stressful situations, and it is better correlated to the cardiotocographic findings than the umbilical arterial pH (11,12). Although there was an association between fetal acidemia and high potassium levels in cord blood, there was no correlation between aldosterone and potassium levels, suggesting that umbilical cord aldosterone concentrations are not related to potassium levels.…”
mentioning
confidence: 99%